EFL STUDENTS’ NEEDS IN ESSAY WRITING THROUGH THE PROCESS-GENRE BASED APPROACH (PGBA) - Khidayatul Munawwaroh; Refnaldi Refnaldi; Hamzah Hamzah; Roslinawati Binti Mohd Roslan (Universitas PGRI Sumatera Barat, 2026)
This study explores the needs of EFL students in essay writing as an initial step toward the development of instructional materials grounded in the Process Genre-Based Approach (PGBA). Specifically, it seeks to examine students’ writing difficulties (lacks), learning preferences (wants), and expectations (goals) in order to inform the design of writing materials that are meaningful and responsive to their learning context. A mixed-methods design was employed, involving 42 EFL students and three lecturers teaching writing courses at a public university in Indonesia. Data were obtained through a 25-item questionnaire and semi-structured interviews. Descriptive statistics were used to analyze the quantitative data, while the qualitative data were analyzed thematically. The findings suggest that students frequently struggle with organizing their ideas, developing coherent paragraphs, and applying grammatical structures accurately. At the same time, they show a clear preference for guided instruction, the use of model texts, and writing activities supported by feedback. In terms of expectations, students express a strong interest in writing materials that are structured, reflective, and motivating. These findings suggest that PGBA is well-suited to addressing students’ needs, as it combines process-oriented writing with genre awareness and provides systematic scaffolding throughout the recursive stages of writing. Overall, the study demonstrates that the principles of PGBA align closely with students’ needs and expectations, supporting its use as a pedagogical framework for EFL writing instruction and materials development.